Aid, conflict, and peacebuilding in Sri Lanka, 2000-2005 - Goodhand, Jonathan; Asia Foundation (Colombo : The Asia Foundation, 2005)
Study funded by various intergovernmental and international agencies.
"Six-part series, volume no. 1."--Cover.
Keywords: Conflict management -- Sri Lanka; Peace-building -- Sri Lanka; Economic assistance -- Sri Lanka